Polymer-Based Composite as a Local Drug Delivery System for Periodontitis Therapy: A Brief Review - Dewi, Agustina; Herda, Ellyza; Sunarso, Sunarso (Syntax Literate, 2024)
Periodontitis is a common chronic oral disease which if left untreated may cause mobility to loss of teeth. Periodontitis is local infection so a therapy using a local drug delivery system was more convenient than a conventional drug delivery system because the probability of side effects emergent is bigger. There are some drug delivery system types in periodontitis therapy and basically, these systems are using a polymer as a matrix by inserting a therapeutic agent into it so creating a composite structure. This study aims to provide a brief review of polymer-based composites utilized as local drug delivery systems for periodontitis therapy. A comprehensive literature review was conducted to gather information on the various types of polymer-based composites employed in periodontitis therapy. Key aspects such as polymer selection, drug loading methods, and therapeutic efficacy were analyzed. The results show Polymer-based composites have shown significant potential as effective local drug delivery systems for periodontitis treatment. The choice of polymer matrix, drug incorporation techniques, and release kinetics play crucial roles in determining the therapeutic outcomes. Various polymers, including biodegradable and non-biodegradable ones, have been explored for their suitability in this application, with promising results reported in preclinical and clinical studies.